LISTA COMENTADA DE LOS MAMÍFEROS TERRESTRES DEL ESTADO DE JALISCO, MÉXICO - Guerrero, Sergio; Cervantes, Fernando A. (Instituto de Ecología, A.C., 2003)
The State of Jalisco has been recognized as one of the richest states in Mexico about the number of mammalian species. Jalisco is located in one of the most remarkable geographic regions, due to the high number of endemisms that occur there. Here we present a checklist of the land mammals inhabiting Jalisco, with emphasis on their endemism and status of conservation. The information was compiled from national and international scientific collections. We found 155 subspecies, 168 species, 89 genera, 22 families and eight orders. Within the species, 26% are monotypic and 74% are polytypic, 40 are endemic to Mexico, including four endemic to Jalisco. As for their conservation status, 21 species are considered in the Mexican Ecological Norm (NOM-ECOL-059- 2001). Finally, Lepus californicus is recorded from Jalisco for the first time.